Att samtala om det omätbara - Petter Eklund (Svensk Teologisk Kvartalskrift)
This article seeks to explore Jonna Bornemark's philosophy and epistemology to see if it can help us find a language for existential questions that take both religious faith and reason seriously. Bornemark stands in the phenomenological philosophical tradition. She uses the epistemology of Nicholas of Cusa and her philosophy is sometimes close to theology, even if she always keeps a safe distance from religious beliefs. She thinks that an epistemology that builds on scientific evidence alone leads to a reductionistic worldview. Instead, she wants to see the particularity in life. Everything in life cannot be reduced to a general truth. Humans cannot get the whole picture, but always need to relate to what is unknown. I argue that Bornemark's epistemology can be a bridge between reason and faith. Both philosophy and theology would be enriched by a mutual dialogue. What she lacks is a deeper understanding of how religion works in people's lives. She tends to see all religion as an attempt to answer existential questions and wants to reduce it to a relation to the things humans cannot understand. Such a view of religion takes it out of its context and puts it in an abstract philosophical worldview. I argue that faith needs both a relation to the things that are larger than the human mind and a relation to people's lives.